2013
DOI: 10.1108/oir-07-2011-0099
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the search feature effectiveness of the major English and Chinese search engines

Abstract: Purpose -The purpose of this paper to investigate the effectiveness of selected search features in the major English and Chinese search engines and compare the search engines' retrieval effectiveness. Design/approach/methodology -The search engines Google, Google China, and Baidu were selected for this study. Common search features such as title search, basic search, exact phrase search, PDF search, and URL search, were identified and used. Search results from using the five features in the search engines were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Most of them tested the effectiveness by using general topic query. Among the comparisons ever done, were against the keyword-based search engines and the semantic-based search engines [3][4]; commercial search engines against dedicated search engines [5] and English search engines against other language search engines [6][7]. Some researcher also did compare the effectiveness using short queries and long queries [8]; natural language queries [9], reformulated queries [10] and many more.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them tested the effectiveness by using general topic query. Among the comparisons ever done, were against the keyword-based search engines and the semantic-based search engines [3][4]; commercial search engines against dedicated search engines [5] and English search engines against other language search engines [6][7]. Some researcher also did compare the effectiveness using short queries and long queries [8]; natural language queries [9], reformulated queries [10] and many more.…”
Section: Related Workmentioning
confidence: 99%
“…Many comparative studies reported that Google always outperform other search engines [7,11]. As an example result from Deka's evaluation [20] reported that Google has the highest rate of performance, followed by Yahoo and Live, Ask and AOL search engines.…”
Section: Fig 3: a Graph For Average Precision At Nmentioning
confidence: 99%
“…According to the results reported by Tawileh et al (2010), Google's effectiveness was higher than Arabic search engines. In addition, the results of Zhang et al (2013) (2013) indicated that Google's effectiveness was higher than Baidu's. In the light of the present research's findings and some previous studies such as Griesbaum and Spink (2004), Demirci et al (2007), Luyt et al (2009), Deka and Lahkar (2010), and Garoufallou (2012), it can be said that Google performs better.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2013) compared the effectiveness of Google and Baidu search engines. They designed 20 search tasks focusing on the four subject domains, including medicine and health, culture and education, information and technology, and business and economy, with five search tasks assigned for each one.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the authors discovered that the simple search string required considerable manipulation in syntax to produce similar yields among the three interfaces. Other factors to consider in evaluating databases include access to full-text articles and overall ease of use (Ewald, 2004;Mansourian, 2008), user performance, how effectively the search tool retrieves citations, the relevance of those retrievals (Zhang et al, 2013), the search strategy, and the topic of the search (Mansourian, 2008). One overarching conclusion from these studies is not surprising: paid databases function differently than databases that are freely available, and it is important that users familiarize themselves with the idiosyncrasies of the databases they select for research purposes.…”
Section: Introductionmentioning
confidence: 99%